Ответы и объяснения

2013-09-24T11:19:51+04:00
Начну с 7. 
(2x-3)/(6-x)   - (12-2x)/(6-x)
2x-3-12+2x=0
4x=15
x=15/4
x=3,75

6 а) 2+3i-3+i-2+6i=10i-3
б)  \frac{(2+3i)(-3+i)}{2-6i} =  \frac{-6+2i-9i+3i ^{2} }{2-6i} = ; Уже ниже расписали

Лучший Ответ!
  • Участник Знаний
2013-09-24T11:29:01+04:00
6
a)
z1+z2-z3=(2+3i)+(-3+i)-(2-6i) = 2+3i -3+i-2+6i = -3  +10i
б)
z1*z2 / z3 = (2+3i)(-3+i) /(2-6i) =
=(-6-9i+2i+3i^2)(2+6i) / (2-6i)(2+6i)=
=(-9-7i)(2+6i) / (2^2-(6i)^2)= 
=(-18- 54i-14i-42i^2) / (4 +36)=
=(24-68i) /40=
=(6-17i)/10
ну или можно  0.6 - 1.7i

7
(2x-3) /(6-x) - 2 = 0
(2x-3) /(6-x) = 2
2x-3 = 2 (6-x)
2x -3 = 12 -2x
4x = 15
x =15/4 =3,75
x =3,75